IMPLEMENTASI KEADILAN (AL-ADL DAN AL-QISTH) DALAM PUTUSAN PENGADILAN PERSPEKTIF HISTORI-YURIDIS - Mutiara, Mutiara; Talli, Halim; Asni, Asni (Institut Agama Islam (IAIN) Kendari, 2026)
The concept of justice in Islamic teachings is fundamentally rooted in the principles of al-’adl and al-qisṭh, which emphasize fairness, balance, and moral responsibility in legal decision-making. However, in the Indonesian judicial system, law enforcement often tends to rely on a legal-formalist approach that prioritizes procedural legality over substantive justice, creating a gap between normative Islamic justice values and their practical application in judicial decisions. This study aims to analyze the implementation of the principles of al-’adl and al-qisṭh in Indonesian judicial decisions and to evaluate their relevance within the framework of the modern national legal system. This research employs a normative legal research method using historical and juridical-analytical approaches. The analysis is based on a review of Islamic legal literature and national legal frameworks, as well as an examination of the Supreme Court of the Republic of Indonesia Decision Number 46 P/HUM/2018. The results show that Islamic justice values have been substantively internalized in judicial reasoning through the application of proportional justice, the balance of rights and obligations, and an orientation toward public interest (maṣlaḥah), although these principles are not always explicitly articulated using Islamic legal terminology. This study focuses on normative analysis and is limited to a specific judicial decision. This research highlights the potential of al-’adl and al-qisṭh as ethical and philosophical foundations that can strengthen the integration of Islamic justice values within Indonesia’s national legal system while bridging the tension between legal certainty and substantive justice.